SUPERIOR PERFORMANCE IN REACTIVE DISTILLATION METHOD FOR INDUSTRIAL APPLICATION: A CASE STUDY OF ETHYL LACTATE PRODUCTION - Taipabu, Muhammad Ikhsan; Rahanra, Geraldi; Rachmah, Alif Nur Laili; Badaruddin, Sabrianah; Trisnantaria, Tamaratritania C.; Tan, Clarissa (ALE Proceeding, 2025)
Ethyl lactate, a biodegradable and environmentally friendly solvent, offers a sustainable alternative to conventional petroleum-based solvents. This study presents a comprehensive evaluation of ethyl lactate production through both conventional and intensified process designs using rigorous process simulation. The reactive distillation column (RDC) was identified as the most efficient configuration, achieving notable reductions in total capital cost (57.3%) and total operating cost (40.2%) compared to traditional setups. The NRTL thermodynamic model was employed to accurately capture non-ideal behavior among reactive components, and kinetic parameters were validated against experimental data. The results demonstrate that RDC-based process intensification significantly enhances economic performance while promoting sustainable chemical manufacturing, positioning it as a promising approach for future green solvent production.